Implementasi Modul Ajar Bahasa Arab Berdiferensiasi di Madrasah Tsanawiyah - Nuzula, Anisah Firdausi; Muflihah (Al Asma: Journal of Islamic Education, 2024)
This study uses a qualitative approach with a case study design to analyze the implementation of differentiated Arabic language teaching modules at MTs Negeri 4 Sidoarjo. Data were collected through in-depth interviews, classroom observations, and analysis of related documents. The subjects of the study consisted of Arabic teachers and students in classes using the teaching modules. The data analysis technique used was thematic analysis. This study shows that implementing differentiated Arabic language teaching modules improved students' Arabic language skills, especially regarding text comprehension and oral production. The teaching modules designed by considering the differences in students' ability levels allowed teachers to provide a more personalized approach, thus helping students with different levels of ability to develop according to their potential. In addition, the differentiation approach positively increased student motivation and active participation in the learning process. The results of this study provide important implications for the development of the Arabic language curriculum and teaching strategies at the MTs level. Further training is needed for teachers in designing and implementing differentiated teaching modules in order to accommodate the diverse learning needs of students. In addition, this study encourages the development of more innovative and adaptive teaching modules to improve the quality of Arabic language learning in madrasah.